(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Unnatural deaths continue to be a matter of global concern due to their multifaceted implications on society, healthcare and public safety, with varying aetiologies and demographics. This study seeks to explore the distinctive patterns, causes, and demographics associated with unnatural deaths in Western Maharashtra. By juxtaposing these findings with Maharashtra and Indian trends, we aim to elucidate whether this region deviates from established patterns or follows a similar trajectory.